1996
DOI: 10.1016/0014-5793(96)00245-1
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin receptor antagonist, loxiglumide, inhibits invasiveness of human pancreatic cancer cell lines

Abstract: Recently, cholecystokinin has been reported to be important in regulating the growth of pancreatic cancer. We investigated the effect of loxiglumide (LXG), a cholecytskinin receptor antagonist, on the invasiveness of two human pancreatic cancer cell lines. Cells were treated with LXG for 24 h, and examined in the invasion assay. The expression and activity of MMP-9 in supernatants from cancer cells were analyzed by V~estern blotting and zymogram. Interestingly, the invasiveness of cancer cells and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…7 Conversely, treatment of the gastrin receptor-positive murine colon cancer, MC-26, with a gastrin receptor antagonist, proglumide, or enprostil, an agent that blocks gastrin release, significantly inhibits tumor growth. [7][8][9] Similarly, we 10,11 and others 12 have shown that the growth of cholecystokinin (CCK) receptor-positive pancreatic cancers is stimulated with CCK treatment and inhibited by CCK receptor blockade. Collectively, these studies have clearly shown that modulation of cancer growth can occur in various experimental models of receptor-positive GI cancers.…”
Section: Discussionmentioning
confidence: 99%
“…7 Conversely, treatment of the gastrin receptor-positive murine colon cancer, MC-26, with a gastrin receptor antagonist, proglumide, or enprostil, an agent that blocks gastrin release, significantly inhibits tumor growth. [7][8][9] Similarly, we 10,11 and others 12 have shown that the growth of cholecystokinin (CCK) receptor-positive pancreatic cancers is stimulated with CCK treatment and inhibited by CCK receptor blockade. Collectively, these studies have clearly shown that modulation of cancer growth can occur in various experimental models of receptor-positive GI cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we do have additional evidence that stimulation of the CCK-2R in other cell lines, that either endogenously (human embryonic kidney cells) or stably (Chinese hamster ovary cells and NIH3T3 cells) express the CCK-2R, besides stimulating proliferation, again affects cell morphology and migration (C Bierkamp, in preparation). Importantly, there is additional evidence from the use of antiserum and antagonists blocking invasion of human colon and pancreatic cancer cells that favor the idea of the CCK-2R being implicated in invasiveness in vivo (Hirata et al, 1996;Watson et al, 2000). Most of the epithelial cell lines expressing the CCK-2R are Figure 8 (a) The association with the cytoskeleton of the proteins from the adherens junction complex is reduced in cells stimulated by gastrin.…”
Section: Role Of Cck-2r In the Regulation Of Cellular Morphologymentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is therefore a crucial event in the development of cancer and a putative target of cancer therapy (Birchmeier and Behrens, 1994). Previously, an implication of the CCK-2R in invasiveness of transformed cancer cells has been shown (Hirata et al, 1996;Watson et al, 2000). However, direct effects of mature, amidated gastrin (G17-NH2) and its receptor in non-transformed epithelial cells on cellcell and cell -substrate adhesion or motility have been elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro invasion assays were performed using a modification of the methods of Albini et al [11] and Hirata et al [12]. Three types of cell culture inserts (8 mm pore size) were used.…”
Section: Cell Invasion Assaymentioning
confidence: 99%